Olympic Review - Reilly, T. (2000)
One of the privileges of academic life is the freedom to make a commitment to the world outside the University, indeed it is often expected. For me, this commitment has included a formal engagement with the British Olympic Association, culminating in the last two Olympic Games, Atlanta and Sydney. Having been involved in the preparation of teams for both of these events, I can reflect on both Games by way of contrast, and on the impact the research activity within the Research Institute for Sport and Exercise Sciences has made. Since 1992 among my responsibilities as Chair of the BOA's Exercise Physiology Steering Group, was the task of determining the acclimatisation strategy for British participants in both summer and winter Olympics. Guidelines for coping with new environments have to be based on sound science, but then translated into working recommendations. The research on 'body-clocks' and 'jet-lag' at JMU provided the British Olympic Association with a head-start over other European countries. Indeed the BOA provided the means for setting up three studies of jet-lag in travellers to Australia between 1998 and 2000. The opportunity to work on this research was accepted with relish by Ben Edwards, now a Research Fellow in the Research Institute. For those of us included, the appointment meant more week-end and after hours work. In October 1999 it was my turn to test-run our draft recommendations for coping with jet-lag and acclimatising in Australia. The strategy was to base the British team at a holding camp on the Gold Coast of Queensland, then go into the Olympic Village in Sydney as near as possible to competition time for the various sports. Facilities on the Gold Coast were excellent: the waters of the Hinze Dam used by the rowers were the envy of many other nations including the Australians. The track-and field athletes used facilities at the new running track at Griffiths University. In 1996 the British athletes had used the Florida State University's campus at Tallahassee as an acclimatisation camp prior to the Games in Atlanta. At Tallahassee we had been engaged 'hands-on' in monitoring levels of hydration in participants and observing physiological stress levels. The 'day-job' at JMU took priority for a few days as I returned for the University's Graduation Ceremony, in particular to introduce Professor Jan Clarys for his Honorary Fellowship. Then it was back to Atlanta for the competitions, accompanied by Chris Boardman, the last British athlete to leave the U.K. for the U.S.A.. This time the Sydney Games were two months later, Australia was too far away to repeat the half-time respite, but I was able to delay my departure until the Annual Conference of the British Association for Sport and Exercise Sciences (BASES) was over, hosted superbly by Don MacLaren and his team. So on the second day of September it was off to Australia once more, this time with the largest single party, 120 in all, heading for the 'holding camp' on the Gold Coast. Travelling almost anonymously in 1996 was in sharp contrast to this year's journey. The 'stars' strutted nonchalantly around the departure lounge at Heathrow Airport with a virtual aura of 'champion' around them. Linford Christie had his own group within his protective wing, being unusual for him to be likened to a mother hen caring for her chicks, whilst other managers allowed their charges to stroll around the public areas in a leisurely way. On the plane the travellers were obviously attentive to our guidelines, moving around on the plane and regularly doing their stretching exercises to avoid deep vein thrombosis. Life at the 'holding camp' appeared relaxed compared to other training camps I had been to. The design of the whole environment represented a 'home away from home'. To avoid losing focus, there was a 'Sydney simulation' room where athletes and coaches could experience what accommodation was like within the British teams' block at the Olympic Village. Morning meetings with team managers started each day. Any issues or problems were picked up at this stage. The exchanges were succinct lasting only about 10-15 minutes, in contrast to the longer meetings in Tallahassee in 1996. The managers knew their goals, were completely focused on the purpose of the camp and were not distracted by extraneous events. Any issues were handled by the BOA's head-quarters staff quickly and discreetly. The sports science personnel kept to their philosophy of discretion, being available on call as and when required. After all, it was too late now for scientific interventions. Work was unobtrusive, built around discussions with athletes at mealtimes or informally in the athletes' lounge, or (despite the camp being 'dry'), with the coaches in their own evening hideaway where stores of liquor were stashed away.